Growth of Microfinance Institutions in India: A Comparative Study: An Examination of the Growth and Performance of Microfinance Institutions in India (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Microfinance institutions provide financial services such as loans, savings, and insurance to society's needy individuals and small business entrepreneurs who cannot qualify for a standard bank loan. The microfinance industry's gross loan portfolio (GLP) stood at 1,87,386 Rs. crore at the end of March, up 38 per cent year-on-year, said a MFIN report Monday. The total number of microfinance accounts was 9.33 crore at the end of March 2019, showing a growth of 21.9 per cent, said Microfinance Institutions Network (MFIN), an RBI-recognised self-regulatory organisation and industry association of the microfinance industry. Non-Banking Finance Company-Microfinance Institutions (NBFC-MFIs) hold the largest share of portfolio in micro-credit with the total loan outstanding of ₹68,868 crore, which is 36.8 per cent of total micro-credit universe. As on March 31, 2019, aggregated GLP of NBFC-MFIs stood at ₹68,207 crore, 47 per cent year-on-year growth compared to March 2018, said MFIN. It refers to small scale financial services for both credits and deposits that are provided to people firms, who operate at small level and their needs, are confined to small amount of money. The present paper looks at the performance analysis of Indian microfinance institutions. The paper collectively covered various MFIs for the period 2016–2019.